Decolonising qualitative research to explore the experiences of Manitoba's urban Indigenous population living with type 2 diabetes mellitus, obesity and bariatric surgery. Issue 10 (1st October 2020) - Hardy, Krista; Zmudzinski, Marta; Fowler-Woods, Melinda; Shingoose, Geraldine; Fowler-Woods, Amanda; Daeninck, Felicia; Hatala, Andrew; Vergis, Ashley
Abstract : Introduction: Obesity and type 2 diabetes mellitus (T2DM) are growing global health concerns associated with significant morbidity, mortality and healthcare expenditures. Due to histories of colonisation and contemporary marginalisation, Canada's Indigenous populations are disproportionately burdened by obesity, T2DM and many other chronic illnesses. Culturally appropriate research on experiences and outcomes of Indigenous patients undergoing bariatric surgery in Canada is scarce. This qualitative study protocol will use a decolonising approach guided by an Indigenous Elder to explore the perspectives and experiences of urban Indigenous Manitobans with respect to T2DM, obesity and bariatric surgery. This knowledge will guide the development and implementation of culturally sensitive bariatric care. Methods and analysis: Sequential sharing circles (SSCs) and semistructured conversational interviews that have been purposefully designed to be culturally relevant with the guidance of an Indigenous Elder and advisory group (IAG) will be carried out in Winnipeg, Manitoba, Canada. Indigenous adults who are obese (body mass index >35 kg/m 2 ), have T2DM and live in an urban centre will be recruited. Three groups will be investigated: (1) those who have had bariatric surgery; (2) those on the wait list for bariatric surgery and (3) those not associated with a bariatric surgery programme. Each group of 10–12 participants will be guided through a semistructured script led by an Indigenous Elder. Elder-facilitated conversational interviews will also be completed following the SSCs. All content will be audio recorded and transcribed. Thematic analysis will be used to identify emerging patterns using a constructive grounded theory approach. Ethics and dissemination: This study has received ethical approval from the University of Manitoba Health Research Ethics Board. Findings will inform the development and implementation of culturally sensitive programmes at Manitoba's Centre for Metabolic and Bariatric Surgery. Results will be disseminated in peer-reviewed scientific journals, at obesity and Indigenous health conferences, and knowledge sharing ceremonies.